The implication of organizational culture for building organizational identity strategy (Case study of PPID Ministry of Finance) - Reinaldy Ferdiansyah; Andre Noevi Rahmanto; Yulius Slamet (Universitas Negeri Yogyakarta, 2021)
This article was made based on the changing needs of the community for information in the era of information and communication technology. To be able to communicate policies in the field of public information disclosure, the government must be able to realize transparently, effectively, efficiently and accountably. The communication process must be supported by a good and reliable organizational identity. This research was conducted to see the implications of how organizational culture changes in the digital era in the Ministry of Finance's public information service process since 2018. The organizational communication process is used as a liaison for the creation of good relations between organizations and the public. This study uses descriptive analytic research methods with results that explain that organizational culture is important in supporting changes in PPID Ministry of Finance's (PPID MoF) public information service activities in the digital age. The implication can be seen that changes in the PPID MoF organizational identity through the use of social media will depend on the organization's strategy and organizational cultural activities. Furthermore, it is expected that the use of social media can be used as a way to educate and increase public participation in the field of public information services